Effect of a Corrective Exercise Program Based on the National Academy of Sports Medicine's Protocol on Forward Head Angle and Cervical Joint Position Sense in Females With Forward Head Posture - Mahsa Abdolahzadeh; Hassan Daneshmandi (Shahid Beheshti University of Medical Sciences, 2023)
Background and Aims Nowadays, the musculoskeletal disorders and postural problems due to inappropriate postural habits and uninterrupted repetitive movements are important issues in sports medicine. Recently, the National Academy of Sports Medicine (NASM)'s corrective exercise protocol has received attention from scholars. This study aims to evaluate the effect of a corrective exercise program based on NASM's protocol on the forward head angle and cervical joint position sense.Methods This is a quasi-experimental study. Participants were 30 female college students, aged 18-25 years with a forward head angle > 46 degrees, who were randomly divided into two groups of control (N=15, age=20±2 years, height=1.59±3.03 m, weight=58.13±5.08 kg, BMI=22.71±1.41 kg/m2) and exercise (N=15, age= 20.53±1.55 years, height=1.60±0.02 m, weight=60.53±4.10 kg, BMI=23.61±1.20 kg/m2). The exercise group performed corrective exercises for eight weeks, three sessions per week, each for 30-70 minutes, while the control group did not receive any intervention. The lateral photography method was used for measuring forward head posture. The cervical joint position sense was assessed using the target angle repositioning error test before and after corrective exercises. Data were analyzed using paired t-test and analysis of covariance. The significance level was set at 0.001.Results Eight weeks of corrective exercises reduced the forward head angle and target angle repositioning error in the exercise group compared to the control group (P≤0.001).Conclusion Corrective exercises based on NASM's protocol seem to reduce the forward head angle and improve the cervical joint position sense. Therefore, correctional treatment specialists and therapists are recommended to use the program to improve the forward head posture and cervical proprioception in women with this postural deformity.